Growth and Development of Potted Ornamental Chilli (Capsicum annuum L.) with Different Types of Fertilizer and Growing Media - Putra, Bagas Akmala; Suketi, Ketty; Syukur, Muhamad (Journal of Tropical Crop Science, 2017)
Chilli has great potential to be marketed as ornamental potted plants due to their diversity in colours and shape of the fruits. The purpose of this research was to determine the optimum growing media and types of fertilizer to improve the performance of three varieties of potted ornamental chilli, ”Syakira”, “Lembayung”, and “Ayesha”. This research was conducted in Cikabayan greenhouse, Bogor Agricultural University, from December 2016 until May 2017. The experiment was arranged in a split plot design with fertilizer as the main factor (without fertilizer, P0; AB mix; P1, and NPK + Gandasil D, P2) and growing media as sub plots, i.e. charcoal husk : soil : manure (M1), perlite: soil : manure (M1), and cocopeat : soil: manure (M3) with proportion of 2:1:1 (v/v). NPK fertilizer and foliar fertilizer Gandasil D showed the maximum plant height, number of branches, number of flowers and fruits. “Ayesha” treated with AB mix fertilizer had the largest fruit diameter whereas “Syakira” and “Ayesha” had the longest fruit under the same treatment. Ornamental chilli grown on charcoal husk and cocopeat had the maximum number of branches and flowers per plant. “Syakira” grown on charcoal husk with AB mix and NPK + Gandasil D, “Lembayung” using cocopeat with AB mix fertilizer, and “Ayesha” varieties using charcoal husk with AB mix fertilizer were the most preferred by the consumers.